2019
DOI: 10.1038/s41598-018-36847-6
|View full text |Cite
|
Sign up to set email alerts
|

Phaeobacter inhibens induces apoptosis-like programmed cell death in calcifying Emiliania huxleyi

Abstract: The model coccolithophore, Emiliania huxleyi, forms expansive blooms dominated by the calcifying cell type, which produce calcite scales called coccoliths. Blooms last several weeks, after which the calcified algal cells rapidly die, descending into the deep ocean. E. huxleyi bloom collapse is attributed to E. huxleyi viruses (EhVs) that infect and kill calcifying cells, while other E. huxleyi pathogens, such as bacteria belonging to the roseobacter clade, are overlooked. EhVs kill calcifying E. huxleyi by ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 83 publications
6
22
0
Order By: Relevance
“…S2). Taken together, HHQ-treated E. huxleyi cells appear to mirror previous studies in which cellular arrest has been observed in phytoplankton in response to bacterially derived chemical exposure (17,18,(27)(28)(29) as well as nutrient limitation (20)(21)(22). In order to elucidate if the observed cellular stasis is mechanistically similar to those observed previously in the literature, we conducted cell cycle, transcriptomic, and proteomic analyses of HHQ-exposed E. huxleyi.…”
Section: Resultssupporting
confidence: 75%
“…S2). Taken together, HHQ-treated E. huxleyi cells appear to mirror previous studies in which cellular arrest has been observed in phytoplankton in response to bacterially derived chemical exposure (17,18,(27)(28)(29) as well as nutrient limitation (20)(21)(22). In order to elucidate if the observed cellular stasis is mechanistically similar to those observed previously in the literature, we conducted cell cycle, transcriptomic, and proteomic analyses of HHQ-exposed E. huxleyi.…”
Section: Resultssupporting
confidence: 75%
“…huxleyi cells appears to mirror previous studies in which cellular arrest has been observed in phytoplankton in response to bacterially derived chemical exposure 19,20,21,22,23 , as well as nutrient limitation 24,25,26 . Indeed, at the physiological level, the response of E. huxleyi to HHQ parallels phosphorus (P) limitation in phytoplankton (i.e.…”
Section: Cell Cyclesupporting
confidence: 84%
“…Cell death is a third loss factor, but its quantification in marine systems, and aquatic systems in general, remains rare compared to the quantification of sinking and grazing losses. Phytoplankton cell death can be caused by pathogens (Bramucci and Case 2019;Schieler et al 2019) or physiological stress, and a handful of studies indicate that a considerable proportion of phytoplankton cells may not be viable (e.g. Brussaard et al 1995;Veldhuis et al 2001;AgustĂ­ 2004;Berman-Frank et al 2004;RychteckĂœ et al 2014).…”
Section: Introductionmentioning
confidence: 99%